Field notes contributed by Peter C. Petersen, fall 1984 - Petersen, Peter C.et al (1984)
Field notes were contributed by Peter C. Petersen, fall 1984. He sighted 49 species, some documented in separate letters, and some with other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed/flatbed